Political discourse theory in the study of resistance movements: an alternative account of the human rights movement in Argentina - Barros, Mercedes María (2013)
This paper has a twofold objective. Firstly, it aims to shed some light on the emergence and constitution ofthe human rights movement and discourse in Argentina, and secondly, it attempts to show how political discoursetheory can actually contribute to the full understanding of new forms of social mobilization. To do this, it looks at theways the human rights movement has been accounted for by the literature and it points at some of the commonproblems and difficulties found in most accounts. It argues that for a more satisfactory understanding of thisphenomenon, the movement’s emergence should be conceived as the result of a contingent process of politicalarticulation and identification which could have failed in its constitution and success. In this way, it turns to explore thedislocatory effects that prompted the process of popular mobilization, and later, to analyze the discursive conditions that made this new sociopolitical identity possible. Finally, it concludes with some remarks on how drawing on a discoursetheory perspective can help us to understand previously unattended aspects involved in the formation of new forms ofsocial and political mobilization.